Between Books and Bunks: Reimagining the Student Mentor Roles - Muhlison; Rosdiani Nasution, Liah; Roihan Daulay, Muhammad (Islam Realitas: Journal of Islamic and Social Studies, 2025)
This study explores the challenges and potential improvements of the roles and responsibilities of Musyrif/Musyrifah at Ma’had Al-Jamiah UIN Syahada Padangsidimpuan, focusing on the role of active students serving in these positions. Through document analysis, interviews with key stakeholders, and Focus Group Discussions (FGDs), the study identifies a significant imbalance between the academic responsibilities of student Musyrif/ah and their duties in dormitory mentoring and management. The indings of the research suggest that the transitionto full-time Musyrif/ah—individuals who are not concurrently enrolled in academicstudies—has the potential to enhance the effectiveness of the mentoring system and dormitoru management. However, the main challenges such as limited funding and infrastructure become obstacles to the implementasion of this programam. The study also highlights the importance of ongoing training and development programs to improve the competencies and qualifications of Musyrif/ah, including  the integrating technology into their roles. Based on these findings, the researchers recommendstrategic policies such as the recruitment of full-time professional Musyrif/ah, the allocationof special funds for dormitory operations, the provision of certified training, and the strengthening of the performance evaluation system. These reforms are considered essential to optimize the Musyrif/ah system to improve the quality of student guidance and management of Ma’had in Islamic higher education institutions.